A Dynamic LCA Model For Assessing The Impact Of Lead Free Solder - E. V. Verhoef (The Minerals, Metals and Materials Society, 2003)
The proposed EU directive on the restriction of the use of certain hazardous substances in electrical and electronic equipment promotes the substitution of lead in consumer electronics to reduce emissions from lead in the end of life phase. In this paper, the consequences of substituting lead in solders is assessed using the Eco-lndicator-99 method for the examples. The base metal production system is considered as an interconnected network modeled dynamically in Simulink 4 and Matlab 6 (Mathworks Inc 2000), where the recovery and production of metal components of the assessed product partially overlap. This approach requires global modeling of metal production processes and mass balances and resulting allocation choices. It also reveals the susceptibility of LeA scores to different choices in the modeling and data availability and uncertainty. Besides the comparison between lead-free and lead-containing solders, other side effects are revealed. Lead is carrier material for the recycling and production of many co-elements in the interconnected production and recovery system. Substitution may have adverse effects such as temporary shortages of other connected metals that are often not considered in normal LeA assessments, thus leading to erroneous results. The suggested approach provides directions for including these external effects and for further assessment of the environmental effects of substituting lead. This paper shows that in order to assess the environmental aspects of metallurgy, dynamic modeling of the total system is required based on the fundamental thermodynamics in each metallurgical reactor, the basis of this dynamic model. With this the true environmental impact of metallurgy can be explained. In the case of lead free solder, it is shown that the mining of substitutes has a very much larger impact.